(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This paper discusses the main methods of persuasion and inspiration in public speaking. It analyzes the importance of effective communication, including logical arguments, emotional appeal, and credibility. The study also highlights the role of audience awareness, clear language, storytelling, and non-verbal communication. In addition, it explains how repetition, rhetorical questions, and confidence influence the effectiveness of a speech. The paper concludes that successful public speaking requires a combination of techniques to influence both the mind and emotions of the audience.